Pseudomonas aeruginosa Performs Chemotaxis to the Neurotransmitters Serotonin, Dopamine, Epinephrine and Norepinephrine - Elizabet Monteagudo‐Cascales; Andrea Lozano‐Montoya; Tino Krell (Microbial Biotechnology)
ABSTRACT Bacteria use chemotaxis to move to favourable ecological niches. For many pathogenic bacteria, chemotaxis is required for full virulence, particularly for the initiation of host colonisation. There do not appear to be limits to the type of compounds that attract bacteria, and we are just beginning to understand how chemotaxis adapts them to their lifestyles. Quantitative capillary assays for chemotaxis show that P. aeruginosa is strongly attracted to serotonin, dopamine, epinephrine and norepinephrine. Chemotaxis to these compounds is greatly decreased in a mutant lacking the TlpQ chemoreceptor, and complementation of this mutant with a plasmid harbouring the tlpQ gene restores wild‐type‐like chemotaxis. Microcalorimetric titrations of the TlpQ sensor domain with these four compounds indicate that they bind directly to TlpQ. All four compounds are hormones and neurotransmitters that control a variety of processes and are also important signal molecules involved in the virulence of P. aeruginosa. They modulate motility, biofilm formation, the production of virulence factors and serve as siderophores that chelate iron. Additionally, this is the first report of bacterial chemotaxis to serotonin. This study provides an incentive for research to define the contribution of chemotaxis to these host signalling molecules to the virulence of P. aeruginosa.